ДИЛОРОМ АБДУРАҲМОН ШЕЪРИЯТИДА ОШИҚ ВА ИШҚ ТАЛҚИНИ - Жумаева, С. (SCIENCE and SOCIETY, 2024)
The article discusses about the poetic world of Faxriyor’s poetry, which has entered Uzbek poetry with new ways of expression, new poetic thinking, no unexpected metaphors.
Keywords: poetry; poet; lyric; subject; line; word; literary tradition; apprenticeship; harmony. image; meaning; expression; interpretation; skill